DINAMIKA KREATIFITAS SASTRAWAN: PRAMOEDYA ANANTA TOER DALAM SEJARAH SASTRA INDONESIA - Masnia Rahayu (ADISAM PUBLISHER, 2024)
In the creation and production of a literary work there is a process that a writer goes through. The process is the involvement of the work as a reflection and the importance of an era. Every work created by the literary will describe the many events that occurred around his life. One of Indonesia's most famous literaries is Pramoedya Ananta Toer who has created more than 50 literary works and translated more than 42 foreign languages. There is a lot of controversy and polemics behind the many works that Pramoedya Ananta Toer has created. This article discusses how the dynamics of creativity of Pramoedya Ananta Toer as a literary in the development of the history of Indonesian literature. As a literary who has given birth to many literary works and achieved a variety of achievements, Pram's perseverance and quality of listening deserves appreciation and appreciation.